Geopolymer and preparation method thereof
By modifying fly ash-slag polymers with sol-type nano SiO2 and water reducing agent, the problems of large amount of alkali exciter and poor fluidity in the preparation of fly ash-slag polymers are solved, and mechanical properties and flowability are improved. Improvement reduces drying shrinkage and promotes its application in the engineering field.
Patent Information
- Application Number
- CN202411283815.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The large amount of alkali exciter used and poor fluidity in the preparation process of fly ash-slag poly, resulting in high preparation costs and poor working performance, limiting its promotion and application in the engineering field.
Using sol-type nano-SiO2 and water-reducing agent to combine modified fly ash-slag dipolymer, nano-SiO2 is prepared in situ by sol-gel method, and the dipolymer slurry is added to optimize the reaction rate and pores Structure, reduce the amount of alkali exciter, improve mechanical properties and fluidity.
Good mechanical properties and durability are obtained at a lower amount of alkali exciter, which improves compressive strength and flow, reduces drying and shrinkage, and improves the working performance of the earth polymer.
Smart Images

Figure CN119143434A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a geopolymer and a preparation method thereof, in particular to a geopolymer using nano-SiO 2 The invention discloses a fly ash-slag geopolymer modified by a water reducing agent and a preparation method thereof, belonging to the technical field of materials. Background Art
[0002] The global greenhouse effect is becoming more and more serious. 2 As one of the main greenhouse gases, reducing its emissions has become a consensus among countries around the world. As a major carbon emitter, China's cement industry accounts for about 12% of carbon emissions. Therefore, finding new green and environmentally friendly alternative cementitious materials is a top priority for achieving the "dual carbon" goal. In recent years, geopolymers have been considered to be one of the most promising green and environmentally friendly cementitious materials. They are inorganic polymers with a three-dimensional network structure composed of silicon-aluminum tetrahedral structural units. There are many types of raw materials and alkali activators for geopolymers. The mechanical properties of geopolymers prepared using fly ash and blast furnace slag as raw materials and sodium silicate and sodium hydroxide as alkali activators are relatively good. However, there are problems such as large amount of alkali activators and poor fluidity in the preparation process of fly ash-slag geopolymers, which make the preparation cost of geopolymers high and the working performance poor, restricting their promotion and application in the engineering field.
[0003] my country's CO 2 There are many sources of emissions, including CO 2 Emissions are the main CO 2 One of the sources of emissions. In the traditional cement industry, ordinary Portland cement is produced by two grinding and one burning. This process produces a large amount of CO 2 Therefore, finding alternative green and environmentally friendly cementitious materials is one of the current research focuses.
[0004] Geopolymer is widely regarded as a green and environmentally friendly cementitious material with the advantages of low carbon, environmental protection, high temperature resistance, etc. It is widely used in thermal insulation materials, refractory materials and packaging materials. Geopolymer has many raw materials, including fly ash, blast furnace slag, coal gangue, metakaolin, etc. They all have high content of SiO 2 and Al 2 O 3 , which can provide abundant silicon-aluminum precursors for polymerization reactions. Existing studies have shown that the mechanical properties and durability of geopolymers prepared from single raw materials are poor, while the effect of using fly ash and blast furnace slag to prepare geopolymers is better, but a large amount of alkali activators are consumed during the preparation process, and the shrinkage is large and the volume stability is poor. Therefore, attempts have been made to use sol-type nano-SiO 2And water reducer are used to modify fly ash-slag geopolymer to obtain a fly ash-slag geopolymer mix with better performance, providing theoretical support for its further promotion and application.
[0005] Nanomaterials refer to materials that have at least one dimension at the nanoscale (1-100nm) in three-dimensional space or are composed of them as basic units. The first International Conference on Nanotechnology and Nanotechnology held in July 1990 marked the emergence of nanomaterial science as a new branch of materials science, and it has since been widely used in all walks of life. Nanomaterial particles can be traced back to the 1970s, and have since gone through about three stages: the first stage (before 1990), the second stage (1990-1994), and the third stage (1994-present). Nanomaterials were first used in traditional materials, medical devices, electronic equipment, coatings and other fields, and their application and research in the field of civil engineering was relatively late. Nanomaterials have the advantages of small size, high surface activity and chemical reactivity, and large specific surface area. They can significantly improve the microstructure of cement-based materials and are one of the current research hotspots in the field of civil engineering.
[0006] Existing studies have shown that nano-SiO 2 With excellent properties such as high specific surface area and high activity, water reducer can improve the fluidity of fly ash-slag geopolymer. 2 There are problems such as poor dispersibility and easy agglomeration during use. A large amount of alkali activator is required in the preparation process of geopolymer. Excessive use of alkali activator is prone to problems such as efflorescence and poor fluidity. The existence of these problems restricts the application of geopolymer.
[0007] Patent application number 202111061352.4 "A geopolymer solidification material based on fly ash + red mud and its preparation method" discloses a fly ash-red mud geopolymer solidification material and its preparation method. In this mix, fly ash, red mud and cement are used in a certain proportion to prepare geopolymer, and a stable silicon-aluminum network structure skeleton is formed through polycondensation reaction. However, this mix does not use alkaline activators such as water glass and sodium hydroxide, and still uses traditional cementitious material cement as a binder, which has a heavy burden on the environment.
[0008] Patent application No. 202211492427.9 "Anti-efflorescence High-dosage Steel Slag Geopolymer Mortar and Preparation Method" discloses a high-dosage steel slag geopolymer anti-efflorescence mortar modified with commercial silane-modified nano-silica admixture and its preparation method. After modification, the silane-modified nano-silica has better waterproof performance and lower surface energy, but commercial silane-modified nano-silica has defects such as shelf life and inability to prepare geopolymer in situ.
[0009] Patent application No. 202011626802.5 "A nano-silica modified geopolymer anti-corrosion mortar and its preparation method" discloses a nano-silica modified geopolymer anti-corrosion mortar and its preparation method, which has the performance characteristics of waterproof and anti-seepage, high strength and crack resistance, acid resistance, salt-alkali corrosion resistance, high adhesion, etc. It can be used for the facades of foundation projects in saline-alkali areas, bridge piers and dams, ports and docks, exterior walls and roofs of buildings in acid rain areas, and other hydrological projects that require waterproofing, crack resistance, and corrosion resistance. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention provides a sol-type nano-SiO 2 A direct preparation method of fly ash-slag geopolymer composite material modified by composite with water reducer. Firstly, sol-gel method is used to prepare sol-type nano-SiO 2 , add it and water reducer together into fly ash-slag geopolymer slurry and mix evenly, sol-type nano-SiO 2 Providing highly active reactants, the water reducer optimizes the working performance of the geopolymer, thereby accelerating the reaction rate of the geopolymer, making the pore structure denser, and ultimately obtaining better mechanical properties and durability. 2 Compared with the sol-type nano-SiO prepared in situ 2 , can reduce the occurrence of agglomeration, can be evenly dispersed in the fly ash-slag geopolymer slurry, and can keep the geopolymer in good working performance. Compared with other conventional naphthalene-based, melamine-based and other water reducers, the water reducer has unique properties for silica fume, fly ash and blast furnace slag, and can keep the fly ash-slag geopolymer in excellent suspension and fluidity. Therefore, in the sol-type nano-SiO 2 Under the action of two admixtures, fly ash-slag geopolymer can obtain better mechanical properties and durability at a lower dosage of alkali activator, and at the same time has better fluidity.
[0011] According to a first embodiment of the present invention, a geopolymer is provided.
[0012] A geopolymer is prepared from the following raw materials: 3-20 parts by weight of fly ash; 1-10 parts by weight of blast furnace slag; 0.5-10 parts by weight of an alkali activator; nano-SiO 2 0.05-3 parts by weight; water reducing agent 0.01-2 parts by weight; water 0.5-5 parts by weight.
[0013] Preferably, the geopolymer is prepared from the following raw materials: 5-15 parts by weight of fly ash; 2-8 parts by weight of blast furnace slag; 1-8 parts by weight of alkali activator; nano-SiO 2 0.1-2 parts by weight; water reducing agent 0.02-1 parts by weight; water 1-4 parts by weight.
[0014] Preferably, the geopolymer is prepared from the following raw materials: 6-10 parts by weight of fly ash; 3-5 parts by weight of blast furnace slag; 2-5 parts by weight of alkali activator; nano-SiO 2 0.15-1 parts by weight; 0.05-0.5 parts by weight of water reducing agent; 1.5-3 parts by weight of water.
[0015] Preferably, the nano-SiO 2 Sol-gel nano-SiO 2 .
[0016] Preferably, the alkaline activator is a mixture of water glass and sodium hydroxide.
[0017] Preferably, the alkaline activator is a mixture of water glass and sodium hydroxide in a mass ratio of 1:0.1-0.5.
[0018] In the present invention, the water reducing agent is a polycarboxylic acid water reducing agent.
[0019] In the present invention, the fly ash is low-calcium F-type fly ash.
[0020] According to a second embodiment of the present invention, a method for preparing a geopolymer is provided.
[0021] A method for preparing a geopolymer, the method comprising the following steps:
[0022] (1) Sol-type nano-SiO 2 Preparation: First, add glycerol and nitric acid into water, stir evenly, and prepare an acidic solution; then, add tetraethyl orthosilicate into the acidic solution, stir and react, and obtain sol-type nano-SiO 2 ;
[0023] (2) Preparation of geopolymer: Pour fly ash and blast furnace slag into a stirring device and mix them evenly; then pour water, sol-type nano-SiO 2 , water reducing agent, alkali activator, stir; finally pour the slurry into the mold, vibrate to remove air, and cure to obtain geopolymer.
[0024] In the present invention, the pH of the acidic solution in step (1) is 2-4.
[0025] In the present invention, the stirring time in step (1) is 2-12 hours; the mixing in step (2) is specifically stirred for 1-60 minutes, and the vibration time is 1-600 seconds.
[0026] The fly ash-slag geopolymer solidification material and preparation method provided by the invention comprise the following components: fly ash, blast furnace slag, alkali activator, sol-type nano-silicon dioxide and water reducing agent.
[0027] 1. Selection of raw materials
[0028] 1. Fly ash
[0029] The main chemical components of fly ash in this embodiment are SiO 2 、Al 2 O 3 and Fe 2 O 3 According to the national standard "Fly ash used in cement and concrete" (GB / T 1596-2017), fly ash belongs to low-calcium Class F fly ash with a CaO content of 5.46%. In addition to the above-mentioned main chemical components, the contents of the remaining chemical components are shown in Table 1.
[0030] Table 1 Chemical composition analysis of fly ash (XRF)
[0031]
[0032] 2. Blast furnace slag
[0033] The main chemical components of the blast furnace slag in this embodiment are CaO, SiO 2 and Al 2 O 3 The remaining chemical compositions of blast furnace slag are shown in Table 2.
[0034] Table 2 Chemical composition analysis of blast furnace slag (XRF)
[0035]
[0036] 3. Alkali activator
[0037] The alkali activator used in this embodiment is a mixture of two substances, one of which is analytically pure water glass with an initial modulus of 3.3, and its chemical formula is Na 2 O 3 .3SiO 2 , and the second is solid flake sodium hydroxide with a purity of 99%. First, pour water glass into the bucket, then slowly pour in the corresponding sodium hydroxide, stir evenly, seal and store, and let it stand for 24 hours for use. In this example, sodium hydroxide is used to adjust the modulus of water glass, and water glass with a modulus of 1.4 is used as an alkaline activator. The larger the modulus of water glass, the lower its alkalinity, which is not conducive to the dissolution of raw materials and reduces the reaction rate of geopolymers.
[0038] 4. Sol-type nano-SiO 2
[0039] Sol-type nano-SiO 2It is prepared in situ by the sol-gel method. First, diluted nitric acid solution is added to 500 ml of deionized water to acidify it into an acidic solution with a pH of about 3. Then, 75 ml of tetraethyl orthosilicate and an appropriate amount of glycerol are added as dispersants. After covering with plastic wrap, it is placed in a constant temperature oil bath magnetic stirrer. The temperature is set to 60°C and the speed is set to 1083 r / min and stirred for 5 hours. After taking it out, let it stand for one hour and wait for use.
[0040] 5. Polymer water reducer
[0041] The water reducer in this embodiment is a light brown liquid with a pH of 6.5-7.5, an effective solid content of 40%, and a specific gravity of 1.30 at 25° C. The water reducer can effectively reduce the viscosity of the cementitious material, enhance its rheological properties, optimize its suspension properties, and has a good improvement effect on silica fume, fly ash and blast furnace slag.
[0042] 2. Preparation of fly ash-slag geopolymer
[0043] Sol-type nano-SiO 2 Preparation: Prepare deionized water, glycerin, tetraethyl orthosilicate, concentrated nitric acid, beaker, measuring cylinder, dropper and other items in advance. First, add glycerin and nitric acid to deionized water, stir evenly, and prepare an acidic solution with a pH of 3.0. Use a measuring cylinder to measure 500 ml and pour it into a beaker. Then, use a measuring cylinder to measure 75 ml of tetraethyl orthosilicate, pour it into the beaker containing the acidic solution, wrap it with plastic wrap, put it in a constant temperature oil bath magnetic stirrer and stir for 5 hours, and finally turn off the instrument and take it out for use.
[0044] First, weigh the corresponding fly ash and blast furnace slag and pour them into the mixer. After slowly stirring for two minutes, the two raw materials are mixed evenly. Then pour water, sol-type nano-SiO 2 and water reducer, stir slowly for three minutes, then stir quickly for three minutes. Finally, pour the slurry into the mold, vibrate it on a vibration table for 30 seconds to remove excess air inside the slurry, and finally cover it with plastic wrap and put it in a curing box.
[0045] Water reducer is one of the most important admixtures in the construction industry, and has an important influence on the working performance, compressive strength and durability of concrete. Water reducers are divided into ordinary water reducers, high-efficiency water reducers and high-performance water reducers according to their water reducing performance, and are divided into early strength type, standard type and retarding type according to their retarding and strengthening effects. Common water reducers include polycarboxylic acid water reducers, naphthalene water reducers, melamine water reducers, aliphatic water reducers and aminosulfonate water reducers. Although there are many types of water reducers at present, they are basically only suitable for ordinary Portland cement and have poor compatibility with geopolymers. This is mainly due to the difference between the polymerization reaction of geopolymers and the hydration reaction of ordinary Portland cement. The main hydration product of ordinary Portland cement is CSH gel, while the main product of geopolymer is NASH gel with a three-dimensional network structure. At the same time, the viscosity of geopolymer slurry is much greater than that of Portland cement, which makes geopolymers need more effective water reducers to improve their working performance. Secondly, different geopolymer systems have different compatibility with water reducer types and concentrations. These reasons lead to the traditional water reducer having little effect on the lifting effect in geopolymers, or even a negative effect. Therefore, finding a water reducer suitable for fly ash-slag geopolymers is conducive to its promotion and application.
[0046] In situ preparation of sol-type nano-SiO by sol-gel method 2 , and water reducer together to modify fly ash-slag geopolymer, reduce the amount of alkali activator, reduce its drying shrinkage, and improve its volume stability.
[0047] At present, there are few related admixtures suitable for fly ash-slag geopolymers. The water reducer and homemade sol-type nano-SiO 2 The fly ash-slag geopolymer was modified by nano-SiO2 to obtain a fly ash-slag geopolymer with better mechanical properties, improved compressive strength and fluidity, and further reduced drying shrinkage. 2 Compared with water reducing agent, the self-made sol-type nano-SiO 2 It is not easy to agglomerate and the dispersion is more uniform. The polymer water reducer can effectively improve the rheological properties of fly ash-slag geopolymer, making the sol-type nano-SiO 2 It can be better distributed in the fly ash-slag geopolymer, making its structure more compact. 2 The activity is higher, the reaction is more complete, and more effective gelling materials can be formed.
[0048] Compared with the prior art, the technical solution provided by the present invention has the following beneficial technical effects:
[0049] Geopolymer is a polymer material composed of inorganic materials. Under the action of alkaline activators, precursors rich in silicon and aluminum elements are dissolved and reorganized to form inorganic polymers with a three-dimensional network structure. Compared with traditional silicate cement, the production process of geopolymer does not require high-temperature calcination, which can reduce energy consumption and CO 2 It is a new type of green and environmentally friendly cementitious material. There are many kinds of raw materials and alkali activators for geopolymers. The raw materials include volcanic ash, blast furnace slag, fly ash, silicate minerals, etc. The alkali activators include water glass, sodium hydroxide, potassium hydroxide, etc. Among them, fly ash and blast furnace slag are used as raw materials, and water glass and sodium hydroxide are mixed as alkali activators to obtain fly ash-slag geopolymer with good mechanical properties. However, there are few related admixtures suitable for fly ash-slag geopolymer. Therefore, this study tried to use water reducer and homemade sol-type nano-SiO 2 To modify fly ash-slag geopolymer, a fly ash-slag geopolymer with better mechanical properties was obtained, its compressive strength and fluidity were improved, and the drying shrinkage was further reduced.
[0050] And conventional nano-SiO 2 Compared with the self-made sol-type nano-SiO 2 It is not easy to agglomerate, the dispersion is more uniform, and it can be well distributed in the fly ash-slag geopolymer, making its structure more compact. 2 The activity is higher, the reaction is more complete, and more effective gelling materials can be formed. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The sol-type nano-SiO 2 Schematic diagram of the preparation process;
[0052] Figure 2 The compressive strength test results of fly ash-slag geopolymer at different ages were obtained in Example 4 of the present invention;
[0053] Figure 3 The test results of the fluidity of fly ash-slag geopolymer prepared in Example 4 of the present invention are as follows;
[0054] Figure 4 This is a drying shrinkage effect diagram of fly ash-slag geopolymer prepared in Example 4 of the present invention;
[0055] Figure 5 The XRD pattern of the fly ash-slag geopolymer prepared in Example 4 of the present invention;
[0056] Figure 6 FTIR graph of fly ash-slag geopolymer prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.
[0058] Example 1
[0059] The weight ratio of each component is as follows:
[0060] Fly ash 7 parts by weight 1400g
[0061] Blast furnace slag 3 parts by weight 600g
[0062] Deionized water 2 parts by weight 395.3g
[0063] Base activator 2.8 parts by weight 558.2g
[0064] The present invention also provides a method for preparing the fly ash-slag geopolymer, comprising:
[0065] Preparation of alkaline activator: add 14.2g of sodium hydroxide solid to every 100g of water glass with an initial modulus of 3.3, stir well and let stand for 24 hours for use.
[0066] Preparation of fly ash-slag geopolymer: First, put fly ash and blast furnace slag into a mixing pot and stir slowly for two minutes to mix the two raw materials evenly; then add alkali activator and deionized water, stir slowly for 3 minutes, then stir quickly for three minutes, then pour the slurry into the mold, vibrate on a vibration table for 30 seconds to remove excess gas inside, scrape it flat, cover it with plastic wrap, and put it into a curing box for curing until the age.
[0067] Example 2
[0068] The weight ratio of each component is as follows:
[0069]
[0070] The present invention also provides a method for preparing the fly ash-slag geopolymer, comprising:
[0071] Preparation of alkaline activator: add 14.2g of sodium hydroxide solid to every 100g of water glass with an initial modulus of 3.3, stir well and let stand for 24 hours for use.
[0072] Preparation of fly ash-slag geopolymer: First, fly ash and blast furnace slag were placed in a stirring pot and stirred slowly for two minutes to mix the two raw materials evenly; then, alkaline activator, deionized water and sol-type nano-SiO 2, first stir slowly for 3 minutes, then stir quickly for three minutes, then pour the slurry into the mold, vibrate on the vibration table for 30 seconds to remove excess gas inside, scrape it flat, cover it with plastic wrap, and put it in the curing box for curing until the age.
[0073] Example 3
[0074] The weight ratio of each component is as follows:
[0075]
[0076]
[0077] The present invention also provides a method for preparing the fly ash-slag geopolymer, comprising:
[0078] Preparation of alkaline activator: add 14.2g of sodium hydroxide solid to every 100g of water glass with an initial modulus of 3.3, stir well and let stand for 24 hours for use.
[0079] Preparation of fly ash-slag geopolymer: First, put fly ash and blast furnace slag into a mixing pot and stir slowly for two minutes to mix the two raw materials evenly; then add alkali activator, deionized water and water reducer, stir slowly for 3 minutes, then stir quickly for three minutes, then pour the slurry into the mold, vibrate on a vibration table for 30 seconds to remove excess gas inside, scrape it flat, cover it with plastic wrap, and put it into a curing box for curing until the age.
[0080] Example 4
[0081] The weight ratio of each component is as follows:
[0082]
[0083] The present invention also provides a method for preparing the fly ash-slag geopolymer, comprising:
[0084] Preparation of alkaline activator: add 14.2g of sodium hydroxide solid to every 100g of water glass with an initial modulus of 3.3, stir well and let stand for 24 hours for use.
[0085] Preparation of fly ash-slag geopolymer: First, fly ash and blast furnace slag were placed in a stirring pot and stirred slowly for two minutes to mix the two raw materials evenly; then, alkali activator, deionized water, water reducer and sol-type nano-SiO 2 , first stir slowly for 3 minutes, then stir quickly for three minutes, then pour the slurry into the mold, vibrate on the vibration table for 30 seconds to remove excess gas inside, scrape it flat, cover it with plastic wrap, and put it in the curing box for curing until the age.
[0086] Performance Testing
[0087] 1. Compressive strength test
[0088] The test block prepared in Example 1 was demoulded and placed in the center of a universal testing machine for testing. The size of the test block was a cube of 40 mm × 40 mm × 40 mm, and the pressure area was 1600 mm. 2 The test process adopts the force control method, and the speed increases uniformly at a rate of 2400N / s±200N / s until the test block breaks and loses its compressive bearing capacity. The maximum failure load in the whole process is recorded. The compressive strength of the test block is calculated according to the following formula (1).
[0089]
[0090] Where:
[0091] R c is the compressive strength, MPa
[0092] F c is the maximum load at failure, N
[0093] A is the compression area of the test block, m 2
[0094] In the examples, the compressive strength of the test pieces was tested at 3 days, 7 days and 28 days.
[0095] 2. Drying shrinkage test
[0096] The test block size for the drying shrinkage test is a cuboid of 40 mm × 40 mm × 160 mm, and three identical test blocks are prepared in each group. After demoulding, the test blocks prepared in Example 1 are placed in an environment with a temperature of 40°C and a relative humidity of 42% for curing until the age. The data are measured every other day, and the test blocks are numbered, and the first test block placement direction and measurement position are marked. The direction and position points remain unchanged for subsequent tests. The drying shrinkage of fly ash-slag geopolymer is calculated according to the following formula (2).
[0097]
[0098] Where:
[0099] ε at is the drying shrinkage microstrain corresponding to day t;
[0100] L 0 Refers to the actual length of the specimen on the first day after molding;
[0101] L t Refers to the measured length of the specimen on the tth day after molding;
[0102] L refers to the length of the test piece, 160 mm.
[0103] In this example, the length change of the fly ash-slag geopolymer was tested every other day, and the drying shrinkage values of the fly ash-slag geopolymer were recorded in total for the first 27 days.
[0104] The test results are shown in the following table:
[0105] Table 3 Compressive strength and fluidity of fly ash-slag geopolymer
[0106]
[0107] The compressive strength, fluidity and drying shrinkage of fly ash-slag geopolymer at different ages are as follows: Figure 2 , Figure 3 and Figure 4 As shown in the figure, it can be seen that the addition of polymer water reducer and sol-type nano-SiO 2 The mechanical properties of the fly ash-slag geopolymer were significantly improved compared with the control group. Specifically, the fluidity of the 5SF group reached 198 mm, an increase of 22 mm compared with 176 mm in the control group, which further improved the working performance of the fly ash-slag geopolymer. In terms of compressive strength, the compressive strength of the 5SF group at 3 days, 7 days and 28 days was 37.3 MPa, 45.7 MPa and 66.8 MPa, respectively, which was about 50.4%, 24.5% and 32.3% higher than that of the control group. In terms of drying shrinkage, the addition of polymer water reducer and sol-type nano-SiO 2 After that, the drying shrinkage of the fly ash-slag geopolymer in the first 27 days was effectively inhibited, decreasing by about 23.8%.
[0108] SiO in fly ash and blast furnace slag 2 、Al 2 O 3 , CaO and Fe 2 O 3 The chemical bonds of substances such as ions break under the erosion of alkaline activators, among which Si-O-Si bonds break more easily. + , K + The addition of ions will affect the medium ionic strength of the solution. The anionic groups and metal cations in the solution form stable monomers under the action of electrical neutralization, thereby preventing the occurrence of reversible reactions. 2 After being added, it can provide highly active silicon precursors for the polymerization reaction of fly ash-slag geopolymers, form more silicon monomers under the action of alkali activators, provide a material basis for the formation of the reaction, and accelerate the early reaction of fly ash-slag geopolymers.
[0109] As dissolved substances continue to accumulate, the probability of contact between decomposition products increases, and they gradually condense and condense. The condensation rate depends on the concentration of dissolved ions and the necessary conditions for condensation. The raw materials form silicate and aluminate monomers under the erosion of alkaline activators. This process is affected by the pH value of the solution and the activity of the raw materials. The reorganization of silicon-aluminum tetrahedrons forms metastable compounds, which combine with metal cations to form condensation monomers. In this stage, the addition of polymer water reducers improves the fluidity of fly ash-slag geopolymers. The increase in fluidity increases the probability of collision between ions and groups in the slurry. At the same time, due to the sol-type nano-SiO 2 Due to the high activity and high specific surface area, the formation rate of oligomers is accelerated and the pore structure of fly ash-slag geopolymers is continuously optimized.
[0110] As the degree of polymerization increases, solid particles appear and precipitation is produced after condensation. The degree of crystallization at this stage is affected by the mineral composition of the raw materials, the type of alkaline activator and the curing environment. Changes in Si / Al can significantly affect the mechanical properties of aluminosilicate gel in fly ash-slag geopolymers, and water plays a key role in the entire polymerization process. Supersaturated aluminosilicates are formed during dissolution, and are released during the polymerization of oligomers, acting as a reaction medium and existing in the pores of the gel. Water and aluminosilicate gels are called dual-phase, and the reorganization of these structures greatly affects the microstructure of fly ash-slag geopolymers and the development of NASH gels. Secondly, a high content of Ca in the raw materials or alkaline activators + Will partially replace Na + The phenomenon of CASH and NASH gel coexisting is formed. In this stage, due to the sol-type nano-SiO 2 With the addition of water reducer, the fluidity of raw materials after dissolving in alkali activator is improved, the formation of oligomers in fly ash-slag geopolymer is accelerated, and some NASH gel products with structures similar to tobermorite and zeolite are formed. The water molecules released after hardening can provide carriers for the flow of remaining decomposition products. Under the virtuous cycle, the early reaction rate of fly ash-slag geopolymer is accelerated, and the structure becomes denser after the internal pores are optimized, thereby improving the mechanical properties and inhibiting its drying shrinkage.
[0111] Study on curing mechanism:
[0112] 1. XRD of solidified body
[0113] The fly ash-slag geopolymer solidified material with a curing age of 28 days was selected for XRD spectrum analysis. The results are as follows: Figure 5Joseph Davidovits's research shows that geopolymer solidification materials have obvious diffraction peaks between 27° and 29°, which is a typical phenomenon of various types of geopolymers. These materials are composed of a disordered framework formed by the polycondensation of aluminosilicates, and their structure is similar to feldspar glass or zeolite crystals.
[0114] Add sol-type nano-SiO 2 After adding the polymer water reducer, the compressive strength, drying shrinkage and fluidity are greatly improved compared with the control group 5S0. From the XRD spectrum analysis, it can be seen that the peak and width in the red dotted box have a large change, which is related to the quartz phase, indicating that the SiO2 in the geopolymer participating in the reaction 2 Increase. As the SiO 2 As the temperature increases, fly ash and blast furnace slag react with metal cations and hydroxyl ions in the medium to generate more NASH gel.
[0115] 2. FTIR of solidified body
[0116] The fly ash-slag geopolymer solidified material with a curing age of 28 days was selected for FTIR spectrum analysis. The results are as follows: Figure 6 FTIR analysis can be used to determine the molecular structure of substances and identify different compounds by observing that the atoms of chemical bonds and functional groups are in a state of constant vibration or rotation, and their vibration frequency is consistent with the vibration frequency of infrared light. When infrared light irradiates molecules, different chemical bonds and functional groups absorb infrared light of different frequencies and appear in different positions on the infrared spectrum.
[0117] It is generally believed that geopolymers are at 950cm -1 To 1030cm -1 The peaks between the two are related to the products NASH and C-(A)-SH gel. As can be seen from the yellow dotted box in the figure, the four groups of geopolymers in this study all showed obvious absorption peaks in this range, indicating that fly ash-slag geopolymers formed NASH and C-(A)-SH gel products. However, by comparison, it was found that the addition of sol-type nano-SiO 2 After adding polymer water reducer, the area and absorption peak intensity of fly ash-slag geopolymer in this range increased, and the 5SF group was more obvious. 2 The addition of polymer water reducer improves its fluidity and compressive strength at all ages, making the structure of fly ash-slag geopolymer denser, while effectively inhibiting the drying shrinkage of fly ash-slag geopolymer, which is consistent with the macroscopic test results.
Claims
1. A geopolymer, characterized in that: The geopolymer is prepared from the following raw materials: 3-20 parts by weight of fly ash; 1-10 parts by weight of blast furnace slag; 0.5-10 parts by weight of alkali activator; 0.05-3 parts by weight of nano-SiO2; 0.01-2 parts by weight of water reducer; and 0.5-5 parts by weight of water.
2. The geopolymer according to claim 1, characterized in that: The geopolymer is prepared from the following raw materials: 5-15 parts by weight of fly ash; 2-8 parts by weight of blast furnace slag; 1-8 parts by weight of alkali activator; 0.1-2 parts by weight of nano-SiO2; 0.02-1 parts by weight of water reducer; and 1-4 parts by weight of water.
3. The geopolymer according to claim 1, characterized in that: The geopolymer is prepared from the following raw materials: 6-10 parts by weight of fly ash; 3-5 parts by weight of blast furnace slag; 2-5 parts by weight of alkali activator; 0.15-1 part by weight of nano-SiO2; 0.05-0.5 part by weight of water reducer; and 1.5-3 parts by weight of water.
4. The geopolymer according to any one of claims 1 to 3, characterized in that: The nano-SiO2 is a sol-type nano-SiO2 prepared by a sol-gel method.
5. The geopolymer according to any one of claims 1 to 4, characterized in that: The alkaline activator is a mixture of water glass and sodium hydroxide; Preferably, the alkaline activator is a mixture of water glass and sodium hydroxide in a mass ratio of 1:0.1-0.
5.
6. The geopolymer according to any one of claims 1 to 5, characterized in that: The water reducer is a polycarboxylate water reducer.
7. The geopolymer according to any one of claims 1 to 6, characterized in that: The fly ash is low-calcium F-type fly ash.
8. A method for preparing the geopolymer according to any one of claims 1 to 7, the method comprising the following steps: (1) Preparation of sol-type nano-SiO2: First, glycerol and nitric acid are added to water, stirred evenly, and then an acidic solution is prepared; then, ethyl orthosilicate is added to the acidic solution, stirred and reacted, and sol-type nano-SiO2 is obtained; (2) Preparation of geopolymer: Pour fly ash and blast furnace slag into a stirring device and mix them evenly; then pour water, sol-type nano-SiO2, water reducer, and alkali activator and stir; finally pour the slurry into a mold, vibrate to remove air, and cure to obtain geopolymer.
9. The geopolymer method according to claim 8, characterized in that: The pH of the acidic solution in step (1) is 2-4.
10. The geopolymer method according to claim 8 or 9, characterized in that: The stirring time in step (1) is 2-12 hours; the mixing in step (2) is specifically stirred for 1-60 minutes, and the vibration time is 1-600 seconds.
